Perancangan Project Management Office (PMO) Berdasarkan Fungsi PMO, Keberhasilan Proyek, dan Kinerja Organisasi (Studi Kasus PT YZ) - Novianti, Irma; Chumaidiyah, Endang; Mufidah, Ilma (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2023)
The PMO design in this study was carried out because the PMO need to strengthen its function so that the PMO can mobilize its full potential according to organizational goals. This study aims to determine the stages of establishing and implementing PMO Initiation, identifying PMO functions and its indicators, analyzing the importance level of results no. 2 towards improving project results & organizational performance, designing business processes & PMO Initiation SOPs. The methods used are expert judgment, AHP, descriptive statistics and BPMN. The results showed that there were 11 stages of establishing and implementing PMO Initiation, 3 PMO functions, 9 PMO function indicators, each 2 success criteria for improving project outcomes and organizational performance. This research also produces business process designs: division (1), department (5) and PMO (3). The managerial implication gives 3 draft PMO SOPs. This PMO design is based on the identification of PMO functions that affect business processes & it is the first time to be done. Modeling and documenting the business processes that occur can identify bottlenecks and improve cross-functional work alignment throughout project activities [1].Keywords: Design, PMO Functions, Project Results, Organization Performance, Business Process.